Christian Religious Education on the Local Culture of the Tiwah Ceremony in Central Kalimantan in Line with Christian Teachings - Lestari, Reysti Ayu; Hindradjat, Juliana; Sompotan, Dale Dompas (Harati: Jurnal Pendidikan Kristen, 2025)
The learning process of Christian Religious Education is a systematic activity that involves many components in it. The good planning is needed so all these components can be implemented. This research is motivated by the existence of students who are less actively involved when participating in Christian Religious Education because the class is dominated by educators. This research aims to describe the importance for an educator to plan a learning process that can increase the activeness and involvement of students in learning. The research uses descriptive qualitative research methods with a literature study approach. From this research it is concluded that in planning Christian Religious Education learning, an educator needs to: understand the uniqueness of students both in their intelligence and learning styles, formulate learning objectives that are able to facilitate students to be actively involved in learning, use varied learning methods, use supporting learning facilities and infrastructure, and make learning assessments that focus on student activeness.